Compact symmetric objects and supermassive binary black holes in the VLBA Imaging and Polarimetry Survey - Tremblay, Steven; Taylor, G.; Ortiz, A.; Tremblay, C.; Helmboldt, J.; Romani, R. (Oxford University Press, 2016)
We present multifrequency Very Long Baseline Array (VLBA) follow-up observations of VLBA Imaging and Polarimetry Survey sources identified as likely compact symmetric objects (CSOs) or supermassive binary black holes (SBBHs). We also present new spectroscopic redshifts for 11 sources observed with the Hobby-Eberly Telescope. While no new SBBHs can be confirmed from these observations, we have identified 24 CSOs in the sample, 15 of which are newly designated, and refuted 52 candidates leaving 33 unconfirmed candidates. This is the first large uniform sample of CSOs which can be used to elicit some of the general properties of these sources, including morphological evolution and environmental interaction. We have detected polarized emission from two of these CSOs the properties of which are consistent with active galactic nuclei unification schemes.